Long-term memory shapes the primary olfactory center of an insect brain - Benoît Hourcade; Emmanuel Perisse; Jean‐Marc Devaud; Jean‐Christophe Sandoz (2009)
The storage of stable memories is generally considered to rely on changes in the functional properties and/or the synaptic connectivity of neural networks. However, these changes are not easily tractable given the complexity of the learning procedures and brain circuits studied. Such a search can be narrowed down by studying memories of specific stimuli in a given sensory modality and by working on networks with a modular and relatively simple organization. We have therefore focused on associative memories of individual odors and the possible related changes in the honeybee primary olfactory center, the antennal lobe (AL). As this brain structure is organized in well-identified morpho-functional units, the glomeruli, we looked for evidence of structural and functional plasticity in these units in relation with the bees' ability to store long-term memories (LTMs) of specific odors. Restrained bees were trained to form an odor-specific LTM in an appetitive Pavlovian conditioning protocol. The stability and specificity of this memory was tested behaviorally 3 d after conditioning. At that time, we performed both a structural and a functional analysis on a subset of 17 identified glomeruli by measuring glomerular volume under confocal microscopy, and odor-evoked activity, using in vivo calcium imaging. We show that long-term olfactory memory for a given odor is associated with volume increases in a subset of glomeruli. Independent of these structural changes, odor-evoked activity was not modified. Lastly, we show that structural glomerular plasticity can be predicted based on a putative model of interglomerular connections.